Feedback Stabilized Optical Fabry–Pérot Interferometer Based on Twin-Core Fiber for Multidimension Microdisplacement Sensing - Chuanbiao Zhang; Tigang Ning; Jingjing Zheng; Jing Li; Heng Lin; Xuekai Gao; Li Pei (IEEE Photonics Journal, 2017)
A novel optical Fabry–Pérot interferometer (FPI) is proposed and experimentally demonstrated for multidimension microdisplacement sensing (MMS). The sensor structure consists of a section of twin-core fiber with a length of 2.4 cm and a section of feedback fiber (FBF) fabricated by normal single-mode fiber. The end faces of two fibers can be formed as the reflection cavity (RC) of the FPI. Mounting the sensor on translation stages, and moving the FBF in different directions to change the RC, the changing mode interference of the reflected beam can be measured. A maximum microdisplacement sensitivity of 0.954 nm/μm with a higher resolution 0.052 μm was achieved. Due to the advantages of the MMS and simple configuration, the sensor is significantly beneficial to practical application.